Comparative studies of bioactive organosulphur compounds and antioxidant activities in garlic (Allium sativum L.), elephant garlic (Allium ampeloprasum L.) and onion (Allium cepa L.). Issue 10 (19th May 2018) - Kim, Sunyoung; Kim, Dan-Bi; Jin, Wenjie; Park, Junghyuck; Yoon, Wonjin; Lee, Yunyeol; Kim, Soyoung; Lee, Sanghee; Kim, Sungsoo; Lee, Ok-Hwan; Shin, Dongbin; Yoo, Miyoung
Abstract: We evaluated organosulphur compounds in Allium vegetables, including garlic, elephant garlic and onion, using high-performance liquid chromatography. Among organosulphur compounds, elephant garlic had considerable γ-glutamyl peptides, and garlic had the highest alliin content. Onion had low level of organosulphur compounds than did elephant garlic and garlic. In addition, antioxidant capacities were evaluated by oxygen radical absorbance capacity (ORAC) values and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2′-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging assay. The results showed that garlic had the highest antioxidant capacity, followed by elephant garlic and onion. Furthermore, a positive correlation was observed between antioxidant activities and organosulphur compounds ( R  > 0.77). Therefore, our results indicate that there was a close relationship between antioxidant capacity and organosulphur compounds in Allium vegetables. Abstract :